Association of obesity with chronic kidney disease in elderly patients with nonalcoholic fatty liver disease - Luo, Kexue; Bian, Jie; Wang, Qinxian; Wang, Jiesheng; Chen, Fuxing; Li, Hongchun; Jin, Dong (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: This study investigated an association between obesity and impaired renal functions in elderly patients with nonalcoholic fatty liver disease (NAFLD) and evaluated the risk factors for chronic kidney disease (CKD) in these patients. Materials and Methods: A cross-sectional study was performed involving 515 elderly patients (≥ 60 years old) with NAFLD. Demographics, body mass index (BMI), medical history, and laboratory parameters were compared for groups stratified by obesity (≥ 28 kg/m2) or CKD. An association between obesity and CKD was analyzed, and a multivariate logistic regression analysis was conducted for risk factors associated with CKD. Results: In the overall population, 28.7% were obese and 54.8% had CKD; there were more women (58.8%) than men. The prevalence of hypertension and diabetes was similar between the obese and nonobese groups and between the CKD and non-CKD groups. Obese patients had significantly higher levels of serum uric acid and estimated glomerular filtration rates when compared with the nonobese group. When compared with those without CKD, patients with CKD were significantly older in addition to having higher BMI and serum uric acid levels. The multivariate logistic regression analysis indicated that CKD was positively associated with age, BMI, and serum uric acid levels. Conclusion: Elderly obese patients with NAFLD are at a higher risk of CKD. NAFLD patients with advanced age, greater BMI, or higher serum uric acid levels are more prone to developing CKD. The renal function of NAFLD patients should be closely monitored. Cite this article as: Luo K, Bian J, Wang Q, et al. Association of obesity with chronic kidney disease in elderly patients with nonalcoholic fatty liver disease. Turk J Gastroenterol 2019; 30(7): 611-5.